Knowledge, awareness and attitude towards dengue fever outbreaks in the summer - Almuhanna, Rawan; Alobudi, Abdulrahman; Alazdi, Saud; Alghamdi, Hammam; Hindi, Muhab; Ghanim, Abdullah; Fakeih, Elaf; Alharbi, Afnan; Jumbi, Roaa; Banjar, Asem (International Journal of Advances in Medicine, 2018)
Dengue fever is a life-threatening viral infection that has been a public health problem. It is estimated that almost more than one half of the world population live in countries where dengue fever is endemic. Among affected individuals, about 5% develop the fatal dengue shock syndrome and dengue hemorrhagic fever, and almost 20,000 patients die annually with these conditions. Despite the magnitude of the problem, dengue fever is a preventable disease. Prevention can be carried out by elimination of inhabitant mosquitoes, vaccination of vulnerable individuals, and regular health education particularly during outbreaks. Many literatures studies were conducted to evaluate the impact of healthcare education on dengue fever prevention, and many researchers studied the population awareness and attitudes about the disease. Knowledge and awareness varied among different studies, and some factors were reported to influence this knowledge such as gender, socioeconomic status, level of education, and computer literacy. The attitudes also differed among the studies and did not seem to be correlated with the population knowledge about the disease. This article will review the knowledge, awareness, and attitudes among different countries towards dengue fever outbreaks in the summer.